Complete Blood Count Parameters in Apheresis Platelet Donors According to ABO and Rh Blood Groups - Gülden Sincan; Fuat Erdem; Elif Bulut; Suat Sincan (Bagcilar Medical Bulletin, 2022)

(untitled)
Objective:Data about the effects of blood groups on complete blood count parameters are limited. We aimed to examine the relationship between complete blood count parameters and ABO-Rh blood groups in this study.Method:Three thousand volunteer apheresis donors were examined. The records of these cases were evaluated retrospectively and age, gender, complete blood count parameters, and ABO and Rh blood groups were recorded. Statistical evaluations were made by the SPSS 21 program.Results:A significant correlation was found between the ABO blood group and erythrocyte distribution width-standard deviation and plateletcrit values (p=0.01, p=0.009, respectively). Neutrophil and mean erythrocyte hemoglobin concentration values were statistically significantly higher in Rh-negative cases than in Rh-positive cases (p=0.04, p=0.01, respectively). Neutrophil count was lower in the A blood group than in the non-A blood group (p=0.03). Lymphocyte count was significantly higher in cases with the B blood group than in cases with the non-B blood group (p=0.002).Conclusion:We found a significant relationship between ABO and Rh blood groups and some complete blood count parameters. Therefore, one of the factors affecting hemogram parameters may be ABO and Rh blood group.